Transient thermodynamic response and boiling heat transfer limit of dielectric liquids in a two-phase closed direct immersion cooling system. (1st October 2021) - Li, Xingping; Lv, Lucang; Wang, Xinyue; Li, Ji
Highlights: A two-phase closed immersion cooling system was fabricated and tested. Three typical dielectric coolants were charged in the cooling system. Boiling crisis was explored and critical heat fluxes were identified. Modified Rohsenow boiling heat transfer equation was established. A universal thermal resistance network was proposed for immersion cooling. Abstract: The heat flux of power electronics is dramatically increasing due to their improving performances and diminishing sizes. Reliable and efficient heat dissipation is one of the key issues which are restricting the development of power electronics. In this paper, a highly efficient two-phase direct immersion cooling system, in which the heat source and the coolant directly contacted with each other, was investigated experimentally. Three different dielectric liquids (ethanol, FC-72, and R113) were employed as the working fluid, and their thermal performances were compared. The results showed that under forced air convection, the minimum total thermal resistance of 0.073 °C/W was obtained at a 1000 W heat load for ethanol. While under natural convection, the minimum total thermal resistance was attained with ethanol as well, and the minimum value is 0.2 °C/W (at the heat load of 300 W). In addition, the heat transfer limits and boiling risks were explored experimentally, and the corresponding critical heat fluxes of the three coolants were analyzed theoretically. The coefficients in our modified Rohsenow boiling heat transfer equation were refitted, with significantly improvement in the accuracy of theoretical modelling for direct immersion cooling.